Aquisição e construção de modelos estáticos análogos a reservatórios petrolíferos com tecnologia lidar e georadar - Teixeira, Washington Luiz Evangelista (2008)
The present work develops a methodology to establish a 3D digital static models petroleum reservoir analogue using LIDAR and GEORADAR technologies. Therefore, this work introduce The methodolgy as a new paradigm in the outcrop study, to purpose a consistent way to integrate plani-altimetric data, geophysics data, and remote sensing products, allowing 2D interpretation validation in contrast with 3D, complexes depositional geometry visualization, including in environmental immersive virtual reality. For that reason, it exposes the relevant questions of the theory of two technologies, and developed a case study using TerraSIRch SIR System-3000 made for Geophysical Survey Systems, and HDS3000 Leica Geosystems, using the two technologies, integrating them GOCAD software. The studied outcrop is plain to the view, and it s located at southeast Bacia do Parnaíba, in the Parque Nacional da Serra das Confusões. The methodology embraces every steps of the building process shows a 3D digital static models petroleum reservoir analogue, provide depositional geometry data, in several scales for Simulation petroleum reservoir